298 Domiciliary periodic Levosimendan infusions in advanced heart failure: a single centre experience. (8th December 2021) - Blasi, Federico; Seganfreddo, Francesca; Croce, Francesca; Morello, Matteo; Oliva, Carlo Agostino; Refugjati, Taulant; Golino, Michele; Cadonati, Cristina; Ceriani, Francesca; Marazzato, Jacopo; Vecchi, Andrea Lorenzo; Ponti, Roberto De
Abstract: Aims: There are several studies that describes a possible use of periodical infusions of Levosimendan in patients with advance heart failure (AHF). In these studies, Levosimendan was administered in ambulatory settings (LevoRep, LION-HEART) or during 24 h of hospital stay (LAICA) and for a maximum of 12 months. Currently there is no strong evidence about the feasibility and safety of performing the infusions in an out of hospital setting. Aim of our study was to analyse the feasibility and safety of periodical Levosimendan infusions in AHF patients, in an out of hospital setting for palliative use. Methods and results: Aretrospective study was conducted from June 2016 to September 2021 on AHF patients, followed by our centre for periodic infusion of Levosimendan. All patients were previously implanted with an ICD, were ineligible for heart transplant or for ventricular assist devices. All patients on each cycle underwent a cardiological evaluation, a blood sample (complete blood count, biochemical profile, coagulation profile, and NTproBNP), and Levosimendan was administrated with a wearable infusion pump (CADD-Legacy ® ; Smiths Medical). The patient went home and came back the day after, to return the pump and for reassessment. We collected data on the different infusion regimen, adapted for every patient, and on adverse events during infusions. We enrolled 11 patients with AHF, 9 (82%) of which of ischaemic origin, 2 (18%) were female, median age 72 years (IQR: 64–75), 10 with NYHA class III, 1 with a NYHA class IV, for a total of 231 infusions, with a median Follow-up of 459 days (IQR 132; 783). A total dose of 6.25 mg was administered at 0.05 μg/kg/min in 24 h. In five patients the infusion was of 12.5 mg at 0.1 μg/kg/min rate in 24 h and in other three patients at 0.05 μg/kg/min in 48 h. The median interval between administrations was 21 days (IQR: 14–24.5). Mild adverse events (i.e. that did not contraindicate successive cycles) were 7 on 231 infusions (3.0%): symptomatic hypotension (four cases, 1.7%), loss of consciousness (two cases 0.9%), bleeding for vein access misplacement (one case, 0.4%). No serious adverse event such as sustained or malignant arrhythmia, allergic reaction, or need for hospital admission were recorded. Conclusions: The administration of Levosimendan at home with a wearable iv pump is safe and well tolerated. This practice allows to reduce infusion costs of day hospital regime and to lengthen the time available for drug infusion, thus reducing the events caused by a too rapid infusion.